Beyond dichotomous thinking: a process perspective on diabetic foot disease. Issue 1 (1st January 2017) - Jarl, Gustav; Lundqvist, Lars-Olov
ABSTRACT: Background : Diabetic foot (DF) disease causes severe suffering around the world, and appropriate self-care activities are needed to prevent and treat this condition. However, all too often, self-care activities are less than optimal and clinicians find themselves unable to influence them in a positive direction. Clinicians' and researchers' mental models of the DF tend to be dichotomous: either the patient has or does not have an active ulcer or other DF disease. This mode of thinking hides the long-term perspective of DF disease, where patients' previous experiences and expectations for the future influence their current behavior. Thus, there is a need for a different perspective on DF disease to better understand patients' perspectives and thereby improve self-care, leading to more effective prevention and treatment. Objective : To present a novel framework, the process perspective on the DF, which can explain inadequate self-care behaviors not easily understood with a dichotomous perspective, and how they can be changed. Results : Three fictive clinical examples are used to illustrate how the process perspective on the DF can be used to understand how patients' previous experiences and expectations for the future influence their current behavior. In particular, this process perspective is used to understand how patients' beliefs and behaviors are sometimes self-reinforcing, resulting in stable behavior patterns, here referred to as 'DF cycles'. These cycles are quite common in clinical practice but are difficult to analyze using a dichotomous perspective on DF disease. The process perspective on the DF is used to analyze specific 'vicious' DF cycles of inadequate patient behavior and to find ways to transform them into 'virtuous' DF cycles, resulting in effective prevention and treatment. Conclusions : The process perspective on the DF seems suitable for understanding inadequate patient behaviors not easily understood with a dichotomous perspective on DF disease, opening up new avenues for clinical practice and research to help patients live a life with long remission phases, few relapses, and a high quality of life.